Metabolomics Methods and Protocols - Weckwerth, Wolfram; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2007)
Metabolomics: Methods and Protocols examines the state-of-the-art in metabolomic analysis. Leading researchers in the field present protocols for the application of complementary analytical methods, such as gas chromatography-mass spectrometry (GC-MS). Metabolomics: Methods and Protocols contains forward-looking protocols, which provide the essential groundwork for future efforts in elucidating the structure of the unknowns detected in metabolomic studies. Part I of this volume focuses on GC-MS techniques; specifically, attention is given to metabolite profiling in blood plasma, construction and application of mass spectral and retention time index libraries, and metabolomic profiling of natural volatiles. In Part II, emphasis shifts to data integration and data mining techniques, and specific protocols discuss improving pattern recognition and biomarker selection for systems level approaches, and visualization and analysis of molecular and metabolomic data. Parts III, IV, and V examine the coupling of capillary electrophoresis and mass spectrometry, classical reversed phase liquid chromatography-mass spectrometry, and electrochemical detection of metabolites using HPLC separations coupled with coulometric electrode array detectors. In Part VI, protocols for the determination of metabolic flux rates are presented and a theoretical framework for metabolic pathway network analysis is provided. The volume concludes with an examination of cutting-edge NMR protocols.
Metabolome Analysis Using Gas Chromatography Coupled to Mass Spectrometry -- Metabolite Profiling in Blood Plasma -- Nonsupervised Construction and Application of Mass Spectral and Retention Time Index Libraries From Time-of-Flight Gas Chromatography-Mass Spectrometry Metabolite Profiles -- Metabolomic Profiling of Natural Volatiles -- Metabolomics: Data Integration and Data Mining -- Integrative Profiling of Metabolites and Proteins -- Integrating Profiling Data -- Visualization and Analysis of Molecular Data -- A Gentle Guide to the Analysis of Metabolomic Data -- Capillary Electrophoresis Coupled to Mass Spectrometry -- Capillary Electrophoresis-Mass Spectrometry for Metabolomics -- Liquid Chromatography Coupled to Mass Spectrometry for Metabolomics and Structural Elucidation -- Application of Liquid Chromatography-Mass Spectrometry Analysis in Metabolomics -- Electrochemical Detection of Metabolites -- High-Performance Liquid Chromatography Separations Coupled With Coulometric Electrode Array Detectors -- Metabolic Fluxes -- Determination of Metabolic Flux Ratios From 13C-Experiments and Gas Chromatography-Mass Spectrometry Data -- Understanding the Roadmap of Metabolism by Pathway Analysis -- NMR Metabolome Analysis -- Revealing the Metabolome of Animal Tissues Using 1H Nuclear Magnetic Resonance Spectroscopy -- Nuclear Magnetic Resonance Metabonomics -- Practical Aspects of Uniform Stable Isotope Labeling of Higher Plants for Heteronuclear NMR-Based Metabolomics.
Keywords: Bioinformatics; Bioinformatics